Ethnomathematics exploration of Panataran Temple and its implementation in learning - Munthahana, Jayanti; Budiarto, Mega Teguh (Universitas Islam Negeri Raden Intan Lampung, 2020)
Mathematics and culture are inherently interconnected, with cultural heritage playing a vital role in shaping national identity and pride. Understanding the mathematical concepts embedded in cultural artifacts enhances meaningful learning and helps preserve local traditions. This study explored the ethnomathematical elements found in Panataran Temple and examined how these mathematical concepts can be integrated into learning to promote mathematical understanding and cultural appreciation. This study employed a qualitative research design with an ethnographic approach using observation, interviews, literature review, and documentation. Data validity was ensured through triangulation. The research identified mathematical concepts embedded in architectural structures, such as Bale Agung, Pendhopo Teras, Angkatahun Temple, Naga Temple, Induk Temple, and the Palah Inscription. Additionally, it examined cultural aspects related to technology, religion, art, language, and social organization. The findings reveal the presence of mathematical elements, including cuboids and quadrilateral prisms, numerical systems, geometric transformations, and probability. These elements serve as tangible learning resources applicable across various educational levels. The study concludes that integrating ethnomathematics into mathematics education enhances students' conceptual understanding while fostering cultural awareness. Its implications highlight the significant role of cultural heritage in mathematics education, promoting meaningful learning and cultural preservation amid the challenges of the disruptive era.